Hispanic Caregivers of the Money Follows the Person Program in Connecticut: Satisfaction, Familism, and Burden. Issue 1 (February 2022) - López-Anuarbe, Mónika; Shugrue, Noreen; Baker, Kristin; Robison, Julie
Hispanic caregivers provide more assistance than the U.S. average, but underutilize support services and report low levels of program satisfaction. A possible exception is the Money Follows the Person (MFP) program. Using an ordered logit statistical approach, we studied program satisfaction of all Hispanic caregivers assisting Connecticut MFP participants from 2014 to 2019, examining the effects of caregiver familism, burden, and personal characteristics including self-reported health and perceived financial situation. Healthier caregivers with positive perceptions of MFP's usefulness and lower subjective burden reported higher program satisfaction. In ordered logits for separate blocks, familism elements (finding caregiving worthwhile, feeling well-supported as a caregiver, and having a good relationship with the care recipient) were statistically significant and associated with higher satisfaction. Our exclusive focus on Hispanic caregivers highlights the role of familism in satisfaction, and demonstrates that programs with a supportive caregiver component can supplement familism ties and overcome barriers to service usage.